Overall Evaluation of the Effects of the 24 January 2020 Sivrice Earthquake (East Anatolian Fault), Turkey - Köküm, Mehmet (Ankara University, 2022)
Turkey is a country where earthquakes are frequent for it is at the junction of a number of tectonic plates. There have been more than 130 recorded destructive earthquakes during the 20th and 21st centuries and they have caused enormous damage. One of the most destructive was the one that hit the east of the country on 24 January 2020. The epicenter of this magnitude 6.8 earthquake was in the town of Sivrice in Elazığ. Sivrice earthquake did not produce primary surface rupture; however, triggered landslides and liquefaction over an area of ~55 km2. The 24 January 2020 earthquake, now known as the Sivrice earthquake, caused substantial human and material losses. Despite the fact that there is a considerable amount of papers available about the Sivrice earthquake, none presents a detailed account of the extensive impact of the Sivrice earthquake its significance. The present study will discuss in detail for the first time the overall impacts of the disaster. It will, therefore, begin with a description of the earthquake and tectonic setting of the area. It then will give an overall assessment of the impact of the earthquake: the direct and indirect losses. Direct effects include all human losses and total or partial destruction of material, as well as the estimated cost of the demolition and clean-up operation required in the region. indirect losses resulted from damage to social and economic infrastructure including accommodation for the homeless, difficulties in transportation and communication, and indirect economic effects. Turkey is highly susceptible to earthquakes and earthquakes related effects due largely to its geological location. Millions of people live in or close to a seismically active area in Turkey for many reasons. It; therefore, will review the policy for sustainable management of earthquakes in Turkey. © 2022, Ankara University. All rights reserved.
Keywords: East Anatolian Fault; Effects of Earthquake; Recovery; Sivrice Earthquake